2021
DOI: 10.3389/fpsyg.2021.577769
|View full text |Cite
|
Sign up to set email alerts
|

Working Under the Gun: A Theoretical Analysis of Stressors Associated With the Re-negotiation of Norms and Control of Work Tasks During COVID-19

Abstract: The COVID-19 pandemic has led many of the world's nations to impose numerous preventive and mitigative measures to increase social distance, including various forms of home isolation and quarantine. A central premise for the current paper is that the COVID-19 situation is likely to constitute a massive re-negotiation of social and organizational norms, which may lead to psychological distress at the individual, family and interpersonal level. Virtually overnight, people have to re-define what is expected and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
(146 reference statements)
0
3
0
Order By: Relevance
“…These current digital developments, reinforced by the COVID-19 pandemic, lead to massive re-negotiation of organizational, social, and behavioural norms, resulting in psychological distress on an individual and interpersonal level (Kant & Norman, 2021). Organizational climate is defined as "the relatively enduring quality of the organization's internal environment that is experienced by members, influences their behavior, and can be described by the values of a particular set of characteristics of the organization" (von Rosenstiel & Nerdinger, 2011, p. 371).…”
Section: Organizational Climate and Culturementioning
confidence: 99%
See 1 more Smart Citation
“…These current digital developments, reinforced by the COVID-19 pandemic, lead to massive re-negotiation of organizational, social, and behavioural norms, resulting in psychological distress on an individual and interpersonal level (Kant & Norman, 2021). Organizational climate is defined as "the relatively enduring quality of the organization's internal environment that is experienced by members, influences their behavior, and can be described by the values of a particular set of characteristics of the organization" (von Rosenstiel & Nerdinger, 2011, p. 371).…”
Section: Organizational Climate and Culturementioning
confidence: 99%
“…(3) The instrumental aspect describes involvement in tasks and hierarchy. Kant and Norman (2021) observed that digitalization caused a power asymmetry regarding hierarchies as individual responsibilities increased but also became less clear.…”
Section: Organizational Climate and Culturementioning
confidence: 99%
“…In many places, the contextual complexity increases as we all engage in work, health, education, and social activities, using the same devices, in the same friendliest-to-video-conferencing spaces in our homes, and challenging expectations and norms about the privacy of our homes in the process. In this sense, previous norms do not necessarily guide us toward what good governance might be, with respect to ICTs (Dwivedi et al, 2020;Kant & Norman, 2021). In this sense, the pandemic not only raises normative contextual boundary management challenges, but also conflates and collapses contexts, introducing new normative challenges.…”
Section: Introductionmentioning
confidence: 99%